Semiotic and discursive analysis of the films Black God, White Devil and Antonio das Mortes, directed by Glauber Rocha - Valverde da Silva, Ana Luiza (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
In 1964, Glauber Rocha directed the film Black God, White Devil year when Brazil suffered a military coup state. Due to strong censorship at the time, the dialogue about political or social issues was forbidden. Despite all that chaos, Glauber Rocha wrote and directed Black God, White Devil and Antonio das Mortes that deal with the dichotomy between good / evil, educated / uneducated, order / disorder, the social, the symbolic constructions of space as semiosphere, borders and their breaks causing chaos. For the director, religion is closely related to politics. The desire for power is enshrined in relations: political and social (interest of the owners on the workers) and religious (priests on the disciples). This analysis discusses on the symbolic dualities, based on the discussion of theoretical semiotics as Yuri Lotman. The goal is to describe how Glauber Rocha built the symbolic spaces over the images and film discourse.